[PP.03.16] INCREASED ROS GENERATION INVOLVES MITOCHONDRIA IN MR-OVEREXPRESSING ADIPOCYTES – IMPACT ON VASCULAR FUNCTION. (September 2016) - Cat, A. Nguyen Dinh; Friederich-Persson, M.; Dulak-Lis, M.G.; Sanchez, A.; Nosalski, R.; Montezano, A.C.; Guzik, T.J.; Jaisser, F.; Touyz, R.M.
Abstract : Objective: Visceral adipose tissue (VAT) influences vascular function through aldosterone and mineralocorticoid receptors (MR). We demonstrated that adipocyte MR over-activation in mice leads to metabolic changes. Whether this is associated with vascular dysfunction remains unclear. Design and method: To address this, we generated mice with conditional MR overexpression targeted to adipocytes (Adipo-MROE) and studied the effect of fat conditioned medium (Fcm, collected from visceral adipose tissue) on vascular reactivity of resistant mesenteric arteries and associated molecular mechanisms. Endothelial-dependent relaxation to acetylcholine (ACh), in the presence or absence of Fcm, was assessed by wire myography. Levels of reactive oxygen species (ROS) were determined in mitochondria isolated from adipose tissues (mito-AT) by electron paramagnetic spin resonance and Amplex Red kit. Inhibitors of NADPH oxidases and mitochondrial ROS were used in our experiments. Results: We previously showed that 1) ROS were increased in adipose tissues from Adipo-MROE vs control (CTR) mice; b) Fcm from Adipo-MROE (Fcm-MR) induced endothelial dysfunction in control arterie, through redox-sensitive mechanisms. Here, we identified the source of ROS in adipocytes, with the hypothesis that NADPH oxidases and mitochondria may play an important role. Levels of superoxide were 3 fold-increased in mito-AT from Adipo-MROE compared to CTR mice (n = 7 mice per group, p < 0.01). We pre-incubated Fcm-MR with either the inhibitor of NADPH oxidase isoforms 1 and 2 (ML171, 10–6 M), either a specific inhibitor of mitochondrial-derived ROS (mito-TEMPO, 10–7 M), and assessed ACh-induced relaxation (10–6 M) in CTR arteries. Normal relaxation was restored by mito-TEMPO (% relaxation: CTR+Fcm-MR, without vs with mito-TEMPO: 47.5 ± 4.4 vs 87.1 ± 2.2, n = 6 mice per group, p < 0.05), whereas Nox1/2 inhibitor-ML171 did not improve endothelial function (% relaxation: 47.7 ± 4.2,  ns). Conclusions: Our data demonstrate that adipocyte MR over-activation leads to increased mitochondrial-derived ROS generation in visceral adipose tissue, which contributes to endothelial dysfunction. We describe a novel mechanism that directly links adipose tissue and vascular function. Our study identifies novel mechanisms linking vascular/adipose tissue biology and aldosterone/MR activation, which may be particularly important in vascular dysfunction associated with metabolic syndrome.